Baicalein as Promising Anticancer Agent: A Comprehensive Analysis on Molecular Mechanisms and Therapeutic Perspectives - Morshed, A K M Helal; Paul, Supti; Hossain, Arafat; Basak, Tuli; Hossain, Md Sanower; Hasan, Md Mehedi; Hasibuzzaman, Md Al; Tanjim, Ishraq Rahaman; Md Abdur, Rashid Mia; Shing, Pollob; Sohel, Md; Bibi, Shabana; et al. (MDPI, 2023)
Despite significant therapeutic advancements for cancer, an atrocious global burden (for example, health and economic) and radio- and chemo-resistance limit their effectiveness and result in unfavorable health consequences. Natural compounds are generally considered safer than synthetic drugs, and their use in cancer treatment alone, or in combination with conventional therapies, is increasingly becoming accepted. Interesting outcomes from pre-clinical trials using Baicalein in combination with conventional medicines have been reported, and some of them have also undergone clinical trials in later stages. As a result, we investigated the prospects of Baicalein, a naturally occurring substance extracted from the stems of Scutellaria baicalensis Georgi and Oroxylum indicum Kurz, which targets a wide range of molecular changes that are involved in cancer development. In other words, this review is primarily driven by the findings from studies of Baicalein therapy in several cancer cell populations based on promising pre-clinical research. The modifications of numerous signal transduction mechanisms and transcriptional agents have been highlighted as the major players for Baicalein's anti-malignant properties at the micro level. These include AKT serine/threonine protein kinase B (AKT) as well as PI3K/Akt/mTOR, matrix metalloproteinases-2 & 9 (MMP-2 & 9), Wnt/-catenin, Poly(ADP-ribose) polymerase (PARP), Mitogen-activated protein kinase (MAPK), NF-κB, Caspase-3/8/9, Smad4, Notch 1/Hes, Signal transducer and activator of transcription 3 (STAT3), Nuclear factor erythroid 2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein-1 (Keap 1), Adenosine monophosphate-activated protein kinase (AMPK), Src/Id1, ROS signaling, miR 183/ezrin, and Sonic hedgehog (Shh) signaling cascades. The promise of Baicalein as an anti-inflammatory to anti-apoptotic/anti-angiogenic/anti-metastatic medicinal element for treating various malignancies and its capability to inhibit malignant stem cells, evidence of synergistic effects, and design of nanomedicine-based drugs are altogether well supported by the data presented in this review study.